2008
DOI: 10.1128/jcm.00027-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional, Nested, and Real-Time PCR Assays for Rapid and Accurate Detection of Vibrio vulnificus

Abstract: We conducted a prospective study to target toxR in the blood of patients with skin and soft tissue infections who were admitted to four tertiary hospitals to assess the clinical usefulness of real-time quantitative PCR (Q-PCR) as a diagnostic technique. We performed conventional PCR (C-PCR), nested PCR (N-PCR), and Q-PCR assays and compared the results to those obtained using the "gold standard" of microbiological culture. The lower detection limit for the Q-PCR assay was 5 ؋ 10 0 copies/l. By use of blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
1
32
1
Order By: Relevance
“…This level of detection would allow for specific and sensitive detection of SMG (6,29,60). The use of universally encoded gene products in our PCR may lead to the potential for false positives (47).…”
Section: Discussionmentioning
confidence: 99%
“…This level of detection would allow for specific and sensitive detection of SMG (6,29,60). The use of universally encoded gene products in our PCR may lead to the potential for false positives (47).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR technology enables quantification of microorganisms (9,16). An association between disease severity/mortality and bacterial DNA load measured by quantitative real-time PCR has been demonstrated for Neisseria meningitidis and Staphylococcus aureus infections (2, 6), but there has been no such study reported for patients with Vibrio septicemia.…”
mentioning
confidence: 99%
“…AF170883). The primers used were tox-130 (T GTTCGGTTGAGCGCATTAA) and tox-200 (GCTTCAGA GCTGCGTCATTC), and the probe was (6-carboxyfluoresc ein-CGCTCCTGTCAGATTCAACCAACAACG-Black Hole Quencher-1) (9,14). V. vulnificus infection was confirmed by identifying V. vulnificus in blood, skin, or soft tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We considered a threshold cycle (Ct; the lowest cycle number to produce a detectable fluorescent signal) value of 38 as the cut-off for a negative result in real-time PCR [12].…”
Section: H33342 Accumulation Assaymentioning
confidence: 99%